2018
DOI: 10.1002/adma.201707077
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Interactions Guided by Shape‐Dependent Hydrophobic Forces

Abstract: Self-assembly of solvated nanoparticles (NPs) is governed by numerous competing interactions. However, relatively little is known about the time-dependent mechanisms through which these interactions enable and guide the nanoparticle self-assembly process. Here, using in situ transmission electron microscopy imaging combined with atomistic modeling, it is shown that the forces governing the self-assembly of hydrophobic nanoparticles change with the nanoparticle shapes. By comparing how gold nanospheres, nanocub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 66 publications
1
45
1
Order By: Relevance
“…Recent reports have focused on in situ imaging of the self-assembly of anisotropic nanoparticles, providing insight into the behavior of nanocubes, 17 branched nanooctapods, 23 and nanoprisms. 24 , 25 In the case of NRs two reports on in situ imaging should be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports have focused on in situ imaging of the self-assembly of anisotropic nanoparticles, providing insight into the behavior of nanocubes, 17 branched nanooctapods, 23 and nanoprisms. 24 , 25 In the case of NRs two reports on in situ imaging should be highlighted.…”
Section: Introductionmentioning
confidence: 99%
“…[ 37 ] It is noteworthy that Au NRs with aspect ratios higher than 3.5 were probably formed spontaneously into the orientational assemblies under the assistance of CTAB. [ 38 40 ] There are several differences between our approach and the previous work. The previous assembly based on CTAB interaction is conducted on solid substrate and the assembly area is limited.…”
Section: Resultsmentioning
confidence: 99%
“…[ 52,53 ] However, many investigations have shown that CTAB molecules presented promoting effects with concentrating Au NRs solution via strong van der Waals (vdW) forces. [ 38 40 ] Therefore, the Au NRs forming multiple assembling morphologies were expected from the interaction between CTAB molecules (Figure 2a – c). As shown in Figure S3, Supporting Information, four assembly modes were revealed according to the interaction manner (sharing a common layer of counterions or interdigitating of CTAB tails from neighboring NPs) of CTAB.…”
Section: Resultsmentioning
confidence: 99%
“…To date, remarkable progress has been achieved on revealing the mechanisms of colloidal NP interactions via different characterization tools, such as small-angle X-ray scattering, 4 zeta potential measurement, 5,10 UV-Vis spectra, 1, 11 and in situ streaming potential measurements. [12][13][14] Recently, liquid cell transmission electron microscopy (LCTEM), as an emerging technique with the capability of imaging at high spatialtemporal resolution, 15,16 has been demonstrated as an effective and feasible platform for investigating the growth, 2,3,17 aggregation, [18][19][20][21][22] etching, [23][24][25] self-assembly, [26][27][28][29][30][31] electrochemical reaction, 32 and bio-application 33 of nanosized objects in aqueous solution.…”
Section: Introductionmentioning
confidence: 99%